Presentations of a numerical semigroup - Özer, Belgin; Kanbay, Sibel (Global Journal of Mathematical Analysis, 2020)
In this paper, we mainly study the minimal presentations of numerical semigroups. Moreover, we examine the concept of gluing, complete intersection, catenary degree, elasticity of some numerical semigroups.Â Â